Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/soru.12308
|View full text |Cite
|
Sign up to set email alerts
|

‘A Woman in Charge of a Farm’: French Women Farmers Challenge Hegemonic Femininity

Abstract: Using data derived from a study focusing on women in southwest France who performed value‐added agriculture, we question to what extent women’s involvement in a male‐dominated occupation, such as farming, provides a context for them to resist normative expectations of hegemonic femininity and to perform alternative forms of femininity. Our findings demonstrate that hegemonic femininity is being challenged and alternative femininities are emerging. Data show both examples of challenges to and compliances with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 60 publications
1
21
0
1
Order By: Relevance
“…The vast majority has an official status on their farm (they were mostly farm operators or cooperators). This is in line with recent research in the French context, showing that when involved in agriculture, women are now more likely to have an official status on their farm (Annes et al, 2021;Le Marchant and Seiller, 2021).…”
Section: Presentation Of the Groupsupporting
confidence: 89%
See 1 more Smart Citation
“…The vast majority has an official status on their farm (they were mostly farm operators or cooperators). This is in line with recent research in the French context, showing that when involved in agriculture, women are now more likely to have an official status on their farm (Annes et al, 2021;Le Marchant and Seiller, 2021).…”
Section: Presentation Of the Groupsupporting
confidence: 89%
“…A multifunctional and sustainable agriculture is now being advocated, the benefits of which go beyond the productive sphere to form part of a more global societal and environmental framework. Several authors have shown that women are more involved in this form of agriculture, which provides them with a suitable framework for reclaiming the frontlines of the agricultural scene (Giraud, 2007;Annes et al, 2021) and thus gain visibility for their work. They are notably more involved in alternative and innovative approaches and bring a new look to the farm through new practices (Giraud and Rémy, 2013;Bessière et al, 2014): short circuits and local markets, organic farming, leisure activities or agritourism (Garcia-Ramon et al, 1995;Giraud, 2007;Brandth and Haugen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is a range of historical and contemporary complexities in farming which has had an impact on how women are perceived as farmers and industry leaders in society (Annes et al, 2021). Both the Australian and international literatures identify that women's work in agriculture is devalued and their contributions within industry are likely to be minimized (Glover, 2014;Alston, 2015;Jackson Wall, 2022).…”
Section: Women's Contribution To Agriculture In Australiamentioning
confidence: 99%
“…Such notions have been perpetuated by "paternalistic attitudes" and gendered divisions of labor between home and work, and the operation of farming work taking place within an environment seen as hostile toward women (Glover, 2014, p. 288;Bossenbroek et al, 2015;Tchékémian, 2022). Women also endure being stereotyped as fragile, inferior or "incomplete, " compared to the image of the male farmer (Rasplus, 2020a;Annes et al, 2021;Jackson Wall, 2022;Savage et al, 2022 p. 30).…”
Section: Women's Contribution To Agriculture In Australiamentioning
confidence: 99%
“…Integrasi agama dan budaya di dalam komunitas lokal masyarakat yang dikombinasikan dengan kreativitas dalam membangun gagasan dan pendampingan kepada perempuan mampu menumbuhkan kepercayaan diri perempuan untuk keluar dari persepsi pragmatis patriarki dan membangun kemandirian ekonominya. Upaya-upaya ini secara kontekstual mampu merespon tantangan-tantangan yang selama ini dialamatkan kepada perempuan seperti, tantangan terkait hak-hak mereka: hak atas tanah dan aset (Akinola, 2018;Aluko, 2015;Folarin et al, 2014), tantangan di sektor informal (Peprah et al, 2019), tantangan dalam wirausaha perempuan (Nguyen et al, 2020;Saner & Yiu, 2019;Uddin, 2021) dan tantangan yang diterima oleh perempuan dalam berbagai bidang (Annes et al, 2021;Khan et al, 2018).…”
unclassified